2002
DOI: 10.1107/s0108768101021607
|View full text |Cite
|
Sign up to set email alerts
|

Amino-substituted O6-benzyl-5-nitrosopyrimidines: interplay of molecular, molecular-electronic and supramolecular structures

Abstract: The structures of eight 2,4,6-trisubstituted-5-nitrosopyrimidines (one of which crystallizes in two polymorphs) have been determined, including seven O6-benzyl derivatives which are potential, or proven, in vitro inhibitors of the human DNA-repair protein O6-alkylguanine-DNA-transferase. In the derivatives having an amino substituent at the 4-position, an intramolecular N—H...O hydrogen bond with the nitroso O as an acceptor leads to an overall molecular shape similar to that of substituted purines. There is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
58
0
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(62 citation statements)
references
References 16 publications
3
58
0
1
Order By: Relevance
“…This trend to the inverse orientation of the pyrimidine planes in the stacking of analogous pyrimidine compounds has been widely observed. [17] Adsorption of Zn 2+ and Cd…”
Section: Complex Formation In Aqueous Solutionmentioning
confidence: 99%
“…This trend to the inverse orientation of the pyrimidine planes in the stacking of analogous pyrimidine compounds has been widely observed. [17] Adsorption of Zn 2+ and Cd…”
Section: Complex Formation In Aqueous Solutionmentioning
confidence: 99%
“…We have recently found that in a number of 2-amino-6benzyloxy-5-nitrosopyrimidines the supramolecular aggregation involves not only conventional hydrogen bonds of NÐ HÁ Á ÁN and NÐHÁ Á ÁO types, but also those of the NÐ HÁ Á Á%(arene) type, where the arene group involved is that of the O 6 -benzyl unit (Quesada, Low et al, 2002;Quesada, Marchal et al, 2002). Since NÐHÁ Á Á%(arene) hydrogen bonds do not occur in all of the 2-amino-6-benzyloxy-5-nitrosopyrimidines which we have studied, we have now undertaken a systematic study of a range of such compounds, carrying a range of amine substituents at the 4-position, in an attempt to discern the conditions under which such interactions are observed.…”
Section: Introductionmentioning
confidence: 99%
“…Since NÐHÁ Á Á%(arene) hydrogen bonds do not occur in all of the 2-amino-6-benzyloxy-5-nitrosopyrimidines which we have studied, we have now undertaken a systematic study of a range of such compounds, carrying a range of amine substituents at the 4-position, in an attempt to discern the conditions under which such interactions are observed. To this end, we present here a study of the molecular and supramolecular structures of (1)±(9) [see Scheme (I)]; of these, (6) has already been discussed elsewhere (Quesada, Marchal et al, 2002) and we refer to it here simply for the purposes of comparison. The amine substituents at the 4-position encompass a relatively wide range of structural diversity, including primary amines bearing linear alkyl substituents [of short, (1), medium, (2) and 7, and large chain length, (3)], cyclohexyl compound (4), phenyl compound (5), and benzyl compound (6), as well as piperidino substituents in (8) and (9) as representative of secondary amines.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies (Low et al, 2000;Quesada et al, 2002;Melguizo et al, 2003) of amino-substituted 5-nitrosopyrimidines have provided compelling evidence for the development of extensively polarized molecular±electronic structures, in which forms such as A (Low et al, 2000) and B (Quesada et al, 2002;Melguizo et al, 2003) (see scheme) make important contributions to the overall molecular±electronic structures, normally represented by forms such as C and D. These polarized structures in turn lead to the formation of supramolecular networks built from charge-assisted (Gilli et al, 1993) hydrogen bonds. With these recent ®ndings in mind, we have now reinvestigated the structure of the title compound, (I) (Fig.…”
Section: Commentmentioning
confidence: 99%
“…
The title compound [systematic name: 6-amino-5-formyl-1,3dimethylpyrimidine-2,4(1H,3H)-dione monohydrate], C 7 H 9 -N 3 O 3 ÁH 2 O, has been reexamined at 120 K. The improved precision of the intramolecular dimensions provides evidence for a polarized molecular±electronic structure, and the molecular components are linked by one NÐHÁ Á ÁO and two OÐ HÁ Á ÁO hydrogen bonds into two interwoven three-dimensional frameworks, which are weakly linked by the longer component of a three-centre NÐHÁ Á Á(O) 2 hydrogen bond.
CommentRecent studies (Low et al, 2000;Quesada et al, 2002;Melguizo et al, 2003) of amino-substituted 5-nitrosopyrimidines have provided compelling evidence for the development of extensively polarized molecular±electronic structures, in which forms such as A (Low et al, 2000) and B (Quesada et al, 2002;Melguizo et al, 2003) (see scheme) make important contributions to the overall molecular±electronic structures, normally represented by forms such as C and D. These polarized structures in turn lead to the formation of supramolecular networks built from charge-assisted (Gilli et al, 1993) hydrogen bonds. With these recent ®ndings in mind, we have now reinvestigated the structure of the title compound, (I) (Fig.
…”
mentioning
confidence: 97%